Monitoring as a tool to evaluate preservation possibilities. Results from the CULTCOAST project - Martens, Vibeke Vandrup; Krangnes, Lars (Frontiers in Earth Science, 2022)
The CULTCOAST research project has installed environmental monitoring equipment at two cultural heritage sites in northern Norway: one at the coal mine site of Hiorthhamn on Svalbard, one at the settlement mound site Sjåberget on Andøya in Nordland County. Both these coastal heritage sites are situated north of the Arctic circle, in the areas most impacted by climate change. Whereas the global temperature increase since 1970 is just above 1 degree Celsius, in Svalbard the increase is now 4 degrees Celsius. This is the first example of using this specific type of sensors to monitor the ongoing changes and their possible impacts on preservation of heritage sites.